Critical Nitrogen Dilution Curve for Diagnosing Nitrogen Status of Cotton and Its Implications for Nitrogen Management in Cotton–Rape Rotation System - Yukun Qin; Weina Feng; Junying Chen; Cangsong Zheng; Lijuan Zhang; Taili Nie (Agronomy, 2025)
Based on a 2-year in situ nitrogen fertilization experiment, this study aims to establish a critical nitrogen concentration (CNC) dilution curve model for cotton under straw incorporation, analyze the effects of the nitrogen application rate on the cotton yield and nitrogen use efficiency (NUE), and determine the optimal nitrogen application rate by integrating the nitrogen nutrition index (NNI). The experiment setup was a randomized block design with five nitrogen application levels under a straw incorporation: 0, 60, 120, 180, and 240 kg N ha−1 (denoted as N0, N60, N120, N180, and N240, respectively). The cotton dry matter accumulation and nitrogen concentration were measured at the flowering and boll stage, peak boll stage, and boll opening stage. The CNC dilution curve was developed using the data from 2021 and validated with those of 2022. Results showed that the cotton biomass and seed cotton yield at the boll opening stage increased with nitrogen application rates up to 180 kg N ha−1. However, no further increase was found in the yield with an N rate higher than 180 kg N ha−1. The CNC dilution curve was formulated as y = 3.4921x−0.416 (R2 = 0.8741). The validation using 2022 data yielded a root mean square error (RMSE) of 0.21% and a normalized RMSE (nRMSE) of 13.40%, confirming the model’s robustness. The NNI, calculated based on the CNC, indicated that an application rate of 120 kg N ha−1 maintained NNI values close to one across all growth stages, reflecting an optimal nitrogen status. Significant positive correlations were observed between the NNI and both the seed cotton yield and harvest index (p < 0.05). Nitrogen use efficiency parameters, including the agronomic NUE (NUEa), nitrogen partial factor productivity (NPFP), and internal NUE (NUEi), exhibited quadratic declines with the increasing nitrogen input. Within the range of 120–240 kg N ha−1, the highest NPFP was achieved at 120 kg N ha−1. In conclusion, the critical nitrogen dilution curve model combined with the NNI effectively diagnoses the nitrogen status in cotton under straw incorporations. Considering the NNI, yield, and nitrogen utilization efficiency, the recommended nitrogen application rate for cotton in a cotton–rape rotation system with a straw incorporation is 120 kg N ha−1.